TAXPAYER COMPLIANCE ON MOTOR VEHICLES IN THE COVID-19 PANDEMI - Arsyil, Abyan; Wiralaga, Harya Kuncara; Pratama, Aditya (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
Given the importance of the role of the community to pay taxes in their participation in bearing state financing, citizen awareness is required to fulfill their state obligations. Apart from awareness as citizens, most people do not fulfill the obligation to pay taxes, especially in the Central Jakarta City area. This study aims to determine the effect of perceptions of tax rates, tax payment methods and tax sanctions on taxpayer compliance in paying motor vehicle taxes. This research was conducted at the Central Jakarta City SAMSATOffice. The number of samples in this study were 234 respondents with the sampling method using the random sampling method. Collecting data in this study using quantitative techniques through questionnaires. The data analysis technique used in this research is multiple linear regression. The analysis used in this study uses IBM SPSS version 24.0. Based on the results of the analysis, it can be seen that tax rates and tax payment methods have no significant effect on taxpayer compliance, while tax sanctions have a positive and significant effect on taxpayer compliance in paying motor vehicle taxes at the Central Jakarta City SAMSATOffice.